Electricity generation from young landfill leachate in a microbial fuel cell with a new electrode material - Ozkaya, Bestamin; Cetinkaya, Afsin Yusuf; Cakmakci, Mehmet; Karadag, Dogan; Sahinkaya, Erkan (SPRINGER, 2013)
This study aims at evaluating the performance of a two-chambered continuously fed microbial fuel cell with new Ti-TiO2 electrodes for bioelectricity generation from young landfill leachate at varying strength of wastewater (1-50 COD g/L) and hydraulic retention time (HRT, 0.25-2 days). The COD removal efficiency in the MFC increased with time and reached 45 % at full-strength leachate (50 g/L COD) feeding. The current generation increased with increasing leachate strength and decreasing HRT up to organic loading rate of 100 g COD/L/day. The maximum current density throughout the study was 11 A/m(2) at HRT of 0.5 day and organic loading rate of 67 g COD/L/day. Coulombic efficiency (CE) decreased from 57 % at feed COD concentration of 1 g/L to less than 1 % when feed COD concentration was 50 g/L. Increase in OLR resulted in increase in power output but decrease in CE.
Keywords: Microbial fuel cell; Landfill leachate; Electricity generation; Coulombic efficiency; WATER; Biotechnology & Applied Microbiology; Engineering